Directions and Priorities for Tourism Development in the Arctic: Content Analysis of Strategic Documents - Svetlana V. Kondrateva; Ekaterina A. Shlapeko (Арктика и Север)
The number of strategic documents has been adopted at the federal level in recent years, establishing the regulatory regime for the development of tourism in the Arctic. At the beginning of the study the key directions and priorities of the tourist development of the Arctic on the federal agenda were identified, and then the strategies of the nine Arctic regions of Russia were considered. The purpose of the work is to determine the key directions and priorities for tourism development in federal and regional policies, as well as to identify the correspondence of regional strategic directions for tourism development with the key directions of tourism development in the Arctic declared by the federal agenda. The study is based on the method of content analysis of regional documents by assessing the qualitative and quantitative presence of keywords chosen by the authors, which made it possible to identify trends that are reflected to varying degrees in regional strategies, concepts, and programs. It was possible to demonstrate common and different features in strategic development of Arctic tourism. The analysis of regional strategic documents on tourism development reveals the existing heterogeneity in content and structure due to the diversity of formats of the documents. The analysis also revealed a lack of assessment of the possibilities and prospects for the development of interregional and intermunicipal cooperation.